Dynamics of Systemic Inflammation as a Function of Developmental Stage in Pediatric Acute Liver Failure - Vodovotz, Yoram; Barclay, Derek; Yin, Jinling; Squires, Robert H.; Zamora, Ruben (Frontiers in Immunology, 2021)
The Pediatric Acute Liver Failure (PALF) study is a multicenter, observational cohort study of infants/children diagnosed with this complex clinical syndrome. Outcomes in PALF reflect interactions among the child’s clinical condition, response to supportive care, disease severity, potential for recovery, and, if needed, availability of a suitable organ for liver transplantation (LTx). Previously, we used computational analyses of immune/inflammatory mediators that identified three distinct dynamic network patterns of systemic inflammation in PALF associated with spontaneous survivors, non-survivors (NS), and LTx recipients. To date, there are no data exploring age-specific immune/inflammatory responses in PALF. Accordingly, we measured a number of clinical characteristics and PALF-associated systemic inflammatory mediators in daily serum samples collected over the first 7 days following enrollment from five distinct PALF cohorts (all spontaneous survivors without LTx): infants (INF, <1 y.o.), toddlers (TOD, 1-2 y.o.), young children (YCH, 2-4 y.o.), older children (OCH, 4-13 y.o.) and adolescents (ADO, 13-18 y.o.). Among those groups, we observed significant (P<0.05) differences in ALT, creatinine, Eotaxin, IFN-gamma, IL-1RA, IL-1b, IL-2, sIL-2Ralpha, IL-4, IL-6, IL-12p40, IL-12p70, IL-13, IL-15, MCP-1, MIP-1alpha, MIP-1beta, TNF-alpha, and NO2-/NO3-. Dynamic Bayesian Network inference identified a common network motif with HMGB1 as a central node in all sub-groups, with MIG/CXCL9 being a central node in all groups except INF. Dynamic Network Analysis (DyNA) inferred different dynamic patterns and overall dynamic inflammatory network complexity as follows: OCH>INF>TOD>ADO>YCH. Hypothesizing that systemically elevated but sparsely connected inflammatory mediators represent pathological inflammation, we calculated the AuCon score (area under the curve derived from multiple measures over time divided by DyNA connectivity) for each mediator, and identified HMGB1, MIG, IP-10/CXCl10, sIL-2Ralpha, and MCP-1/CCL2 as potential correlates of PALF pathophysiology, largely in agreement with the results of Partial Least Squares Discriminant Analysis. Since NS were in the INF age group, we compared NS to INF and found greater inflammatory coordination and dynamic network connectivity in NS vs. INF. HMGB1 was the sole central node in both INF and NS, though NS had more downstream nodes. Thus, multiple machine learning approaches were used to gain both basic and potentially translational insights into a complex inflammatory disease.